EFFECT OF PERCEIVED EASE OF USE, REVENUE AND CUSTOMER PERCEIVED BENEFIT ON CONSUMER BEHAVIOR OF E-WALLET SERVICE USERS ACCORDING TO ISLAMIC PERSPECTIVE (Study on Generation Z GoPay service users in Bandar Lampung) - Hasan, Pramita; Ekawati, Evi; Tegar, Melda (REVENUE: Jurnal Manajemen Bisnis Islam, 2024)
Excessive consumption can affect the financial stability of individuals as well as society in general. This study aims to examine the effect of perceived Ease of Use, income, and Customer Perceived Benefit on consumer behavior of e-wallet service users from an Islamic perspective, especially in Generation Z of GoPay service users in Bandar Lampung. This study uses a quantitative approach with survey methods through questionnaires as a data collection tool. The research sample is GoPay users in Bandar Lampung who are part of Generation Z. The data analysis technique used is multiple regression to test the relationship between the independent variables (Ease of Use, income, and Customer Perceived Benefit) with the dependent variable (consumptive behavior). The Data in this study is the primary data processed using SMART PLS 4 software. The perception of Ease of Use has an original sample value of 0.213 which means that it has a positive relationship and the perception of Ease of Use also has a T-statistical value of 2.110 > 1.661 and a p-value of 0.035 < 0.05 which means that the relationship is significant. It can be concluded that the first hypothesis of the perception of Ease of Use has a positive and significant effect on consumptive behavior. this study is in accordance with the theory of Tam (Technology Acceptance Model) which explains that the idea of Tam (Technology Acceptance Mode)l is an information systems theory that aims to explain how consumers understand and use various data technologies. when a person believes that using a system will make his work easier. convenience can help save time and effort when using a particular technology system because people will find the system or technology easy to use. As a result, transactions will become easier for the general public.   Consumptive behavior is the desire to buy goods or services even though they are not necessary to achieve the highest level of success.